Development of a Novel Squirrel-cage Doffing Robot - Yang Sicheng; Zhang Wenzeng; Cao Liguo (Jixie chuandong)
In order to overcome the disadvantages of present doffing robots,a novel squirrel-cage doffing mechanism is proposed. The principle of the squirrel-cage doffing mechanism is analyzed and the structure model of the mechanism is built. The squirrel-cage doffing mechanism mainly consists of grippers,vertical rails,driving shafts,driving chains,driving wheels and a spatial cam. The reasonable range of the structural parameters of the squirrel-cage doffing mechanism is determined by the motion analysis of the squirrel-cage doffing mechanism. The squirrel-cage doffing robot adopting the squirrel-cage doffing mechanism is developed. The experimental results show that the squirrel-cage doffing robot can pull the cops out of the spindles vertically. During the doffing process,the doffing robot has no damage to the yarn and spindles. The squirrel-cage doffing robot is of low cost,highly efficient and reliable.